Modification of gelatin and photocured 3D‐printed resin to prepare biomimetic phantoms for ultrasound‐guided minimally invasive surgeries - Chen, Chien‐Hua; Huang, Yi‐Fan; Chen, Po‐Hao; Hsu, Yu‐Tung; Jaw, Fu‐Shan; Ho, Ming‐Hua (Polymer engineering and science, 2023)
The main challenge of ultrasound‐guided minimally invasive surgeries is to carry out treatments through small boreholes in the patient's body surface with sub‐millimetric accuracy and facility offered by ultrasound instruments. Thus, the phantoms' biomimetic appearances, acoustic characteristics, and mechanical properties are essential for healthcare professionals. In this study, gelatin and 3D‐printed photo‐resin phantoms were developed for hard and soft tissues, respectively. Using glutaraldehyde (GA) and formaldehyde (FA) to crosslink gelatin phantoms, the mechanical strength, ultrasound velocity, acoustic impedance, needle insertion forces, and antiseptic periods were improved, and the addition of silica nanoparticles raised the acoustic impedance. For 3D‐printed phantoms, the acoustic impedance ascended with hydrophilic polyethylene glycol diacrylate (PEGDA) oligomers. The additives applied in this study successfully made the gelatin and photo‐resin phantoms more mimetic to muscle and bone tissues, allowing their application in preoperative preparations. 3D‐printed photo‐resin phantoms were developed for hard and soft tissues. The additives of crosslinkers, nanoparticles, and reactive monomers improved the mechanical strength, acoustic properties, needle insertion forces, and antiseptic periods of phantoms efficiently.